Exploring the Use TPACK in Teaching Listening - Kristina Rustanto; Dedi Rahman Nur; Rinda Mitriana (Center of Language and Cultural Studies [CLCS], 2020)
This research study Exploring the use of the TPACK framework in listening classrooms. This research focuses on how the teacher develops instrument design in listening classroom with the TPACK framework. Data collection consisted of classroom observation, a checklist with indicator guide and field notes Findings the result there is different the teacher 1 and 2 with developing instrument design in listening classroom with TPACK Framework. The different teacher 1 dominant with CK ( content knowledge) and PK ( pedagogical knowledge) and able to is able to design lesson plan involved technology, taught used technology that appropriates with learning material, and she manages the class by using technology. This the conclusion of the research in SMA Budi Bakti about developing instrument design in the listening classroom with TPACK framework